Taxonomic identification of algal species overgrowing hard corals in Taklong Island National Marine Reserve, Nueva Valencia, Guimaras. - Diola, Sedie Joy Mesa
In a study of algal species that overgrow or otherwise compete with corals, 18 species belonging to 13 genera representing 3 classes of macrobenthic algae were collected from Binabaywan, an extensive reef flat in Taklong Island National Marine Reserve (TINMAR). species were described and characterized using Trono et. al (1988) and Taylor (1979). A species of blue green algae Microcoleus lyngbyaceus was observed to overgrow the colony of Acropora, green flags of Chaetomorpha, the filamentous algae and Codium sp, the encrusting green algae were seen to overgrow the massive hard coral Porites. Chlorodesmis was overgrowing a massive Faviid. Other species of corals identified were the fleshy macroalgae, Halimeda, Turbinaria sp, Galaxaura, Laurencia, Codium sp, Dictyota sp, Actinotrichia, Amphiroa sp that comes in contact with dead hard coral tissue of Faviid.